2018
DOI: 10.1021/acschembio.7b00874
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Application of a Novel Species of Bacillus: Bacillus velezensis

Abstract: Bacillus velezensis has been investigated and applied more and more widely recently because it can inhibit fungi and bacteria and become a potential biocontrol agent. In order to provide more clear and comprehensive understanding of B. velezensis for researchers, we collected the recent relevant articles systematically and reviewed the discovery and taxonomy, secondary metabolites, characteristics and application, gene function, and molecular research of B. velezensis. This review will give some direction to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 62 publications
2
76
0
Order By: Relevance
“…B. velezensis is a new type of biocontrol factor with inhibitory ability against a broad spectrum of microbial pathogens and plant growth promoting activity [63]. It produces various antifungal and antibacterial metabolites including β-1,3-1,4-glucanase, lipopeptides (iturin, fengycin and surfactin), polyketides (macrolactin, bacillaene and difficidin or oxydifficidin) and peptides (plantazolicin, amylocyclicin and bacilysin) [64][65][66][67]. It is reported that lipopeptides produced by B. velezensis are the major contributor to inhibiting pathogenic fungi, such as F. oxysporum, C. gloeosporioides and so on [27,68].…”
Section: Discussionmentioning
confidence: 99%
“…B. velezensis is a new type of biocontrol factor with inhibitory ability against a broad spectrum of microbial pathogens and plant growth promoting activity [63]. It produces various antifungal and antibacterial metabolites including β-1,3-1,4-glucanase, lipopeptides (iturin, fengycin and surfactin), polyketides (macrolactin, bacillaene and difficidin or oxydifficidin) and peptides (plantazolicin, amylocyclicin and bacilysin) [64][65][66][67]. It is reported that lipopeptides produced by B. velezensis are the major contributor to inhibiting pathogenic fungi, such as F. oxysporum, C. gloeosporioides and so on [27,68].…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus species are ubiquitous in nature and occupy diverse ecological niches in microbiomes across soil, water, plants, and humans. Some Bacillus strains play increasingly important roles in microbial remediation and the fermentation industry (48). Considerable numbers of Bacillus strains are potential degraders of various aromatic compounds, such as BP and naphthalene (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus velezensis has been widely used as a biological control agent in agricultural elds due to its excellent ability to suppress plant diseases [24,25]. It is considered as a potential rhizobacterial organism with extraordinary biosynthetic machinery, which can trigger innate immunity in plants [26].…”
Section: Introductionmentioning
confidence: 99%